2002
DOI: 10.2136/sssaj2002.1669
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Harvesting Impacts using Soil Compaction and Disturbance Regimes at a Landscape Scale

Abstract: Several indicators have been identified for the conservation and maintenance of soil criterion in the Montreal Protocol. The objective of this study was to use soil compaction and disturbance measures to determine harvesting impacts at a landscape scale in the boreal forest of Saskatchewan. Forest harvesting impacts were studied pre and postharvest for five harvested sites by (i) sampling soil bulk density (Db) at prescribed grid‐points, and (ii) measuring soil disturbance regimes on two 30‐m transects at each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…The forest floor removal combined with compaction would be most similar to roads within operational cutblocks, ranging from 3% to 5% of the cutblock area (Block et al 2002, MacIsaac et al 2006. Adjacent to roads, repeated machine traffic areas used for processing and loading of logs, but where forest floor would not be removed, can occupy from 4% to 5% (MacIsaac et al 2006) up to 10% to 20% (British Columbia Ministry of Forests, unpublished data) of the harvested area.…”
Section: Tree Growth Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The forest floor removal combined with compaction would be most similar to roads within operational cutblocks, ranging from 3% to 5% of the cutblock area (Block et al 2002, MacIsaac et al 2006. Adjacent to roads, repeated machine traffic areas used for processing and loading of logs, but where forest floor would not be removed, can occupy from 4% to 5% (MacIsaac et al 2006) up to 10% to 20% (British Columbia Ministry of Forests, unpublished data) of the harvested area.…”
Section: Tree Growth Responsesmentioning
confidence: 99%
“…Adjacent to roads, repeated machine traffic areas used for processing and loading of logs, but where forest floor would not be removed, can occupy from 4% to 5% (MacIsaac et al 2006) up to 10% to 20% (British Columbia Ministry of Forests, unpublished data) of the harvested area. When all sources of harvesting disturbance are combined, up to 32% of a harvested opening can have bulk density increases greater than 15% (Block et al 2002). Puettmann et al (2008) used the assumptions that aspen height was only affected in absolute terms for the first 10 years or that the relative height difference was present at the end of the rotation to demonstrate "best case" and "worst case" scenarios.…”
Section: Tree Growth Responsesmentioning
confidence: 99%
“…The severity of soil compaction is site-specific and influenced by slope, season of harvest, soil texture, and soil moisture, which can exacerbate or confound the impacts of heavy equipment on soil properties (Arikian et al 1999, Block et al 2002, Shaw and Carte 2002, Berger et al 2003. In a review of soil compaction studies, Graecen and Sands (1980) concluded that both thinning and clear-cut harvesting are forest management practices most likely to cause soil compaction, although quantitative data on the impact of thinning on soil compaction were not given.…”
Section: Mots Clé Smentioning
confidence: 99%
“…Many studies have found increased soil bulk densities, greater soil PR, and reduced water infiltration rates after a single-cohort (clear-cut) timber harvest (e.g., Mace 1970;Miller et al 1996;Block et al 2002;Shaw and Carte 2002;Scott et al 2004). In contrast, few studies have addressed the effects of stand thinnings or partial cuts on soil compaction, and these have focused mostly on skid trails after one thinning (King and Haines 1979;Landsberg et al 2003).…”
Section: Mots Clé Smentioning
confidence: 99%
“…Soil compaction results in an increase in bulk density (Block et al 2002;Demir et al 2007;Makineci et al 2007), reduction in macroporosity (Rohand et al 2004;Ampoorter et al 2007), saturated hydraulic conductivity (Wood et al 2003; Grace et al 2006), water content, infiltration , N mineralization and microbial number biomass and activity (Ares et al 2005;Tan et al 2008). Each of these features can potentially reduce the tree growth (Froehlich 1979;Corns 1998).…”
mentioning
confidence: 99%